Processing aid for vinyl chloride resin compositions
A processing aid with specific polymer ratios and molecular weights addresses the challenge of achieving both good surface properties and gloss in vinyl chloride resin compositions, enhancing transparency and reducing defects like flow marks and fish eyes.
Patent Information
- Application Number
- JP2022553457
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-05-27
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2041-05-27
AI Technical Summary
Existing processing aids for vinyl chloride resin compositions face challenges in achieving both good surface properties and gloss without causing flow marks and fish eyes, while maintaining transparency and compatibility with the resin, and are often costly.
A processing aid comprising specific ratios and molecular weights of first and second polymers, including alkyl methacrylate and aromatic vinyl compounds, with optional third polymers for improved granulation, is used to enhance compatibility and surface properties without increasing costs.
The solution achieves a balance of good transparency, yellowness, and surface properties by using a processing aid with a specific composition and molecular weight ratio of polymers, reducing flow marks and fish eyes in molded products.
Smart Images

Figure 0007657817000001 
Figure 0007657817000002 
Figure 0007657817000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a processing aid for a vinyl chloride resin composition, a vinyl chloride resin composition and a molded article thereof. [Background technology]
[0002] PVC resins are widely used in various molded products taking advantage of their characteristics, but they have various problems related to processing, such as the processing temperature being close to the thermal decomposition temperature and poor fluidity. In order to overcome these problems, a method has been proposed in which a copolymer mainly composed of methyl methacrylate is blended as a processing aid. This method can promote gelation without reducing the properties of the PVC resin, resulting in molded products with excellent transparency and surface gloss. However, there is a drawback in that flow marks and fish eyes occur on the surface of the calendar sheet and film during calendar processing, reducing the commercial value of the molded product. In addition, methyl methacrylate is relatively expensive among the commonly used (meth)acrylic acid esters, and processing aids using inexpensive raw materials have been required.
[0003] On the other hand, Patent Document 1 proposes a method of adding a processing aid containing a first polymer containing a vinyl cyanide compound and an aromatic vinyl compound, and a second polymer containing an alkyl acrylate and having a low Tg, to a vinyl chloride resin composition. In this method, the gelation time is shortened while maintaining low costs by using styrene, which is an inexpensive aromatic vinyl compound. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2016 / 195013 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the processing aid containing the inexpensive aromatic vinyl compound disclosed in Patent Document 1 has low compatibility with the vinyl chloride resin, which may cause poor kneading, and thus may significantly reduce the gloss of the molded product. In addition, although it is possible to improve the kneading property and improve the gloss by increasing the melt viscosity of the processing aid or the amount of the processing aid added, there is a risk that the surface properties (flow marks and fish eyes) may deteriorate in this case. In other words, the surface properties and gloss of the molded product are in a trade-off relationship, and it is not easy to achieve both. [Means for solving the problem]
[0006] In order to solve the above problems, the present inventors have conducted intensive research and have found that a processing aid containing a first polymer and a second polymer having a specific composition and weight-average molecular weight can be used in a large amount of an aromatic vinyl compound, which is an inexpensive raw material, to favorably achieve both surface properties and gloss of a molded product while maintaining good transparency and yellowness, thereby completing the present invention. The present invention includes the following aspects.
[0007] <1> A processing aid for a vinyl chloride resin composition comprising a first polymer and a second polymer, the first polymer having a weight average molecular weight of 600,000 to 4,000,000 and comprising, based on the total weight of the first polymer being 100% by weight, 60 to 100% by weight of an alkyl methacrylate and 0 to 40% by weight of other copolymerizable vinyl compounds, the second polymer having a weight average molecular weight of 10,000 to 400,000 and comprising, based on the total weight of the second polymer being 100% by weight, 30 to 90% by weight of an aromatic vinyl compound and 10 to 70% by weight of other copolymerizable vinyl compounds, the sum of the first polymer and the second polymer being 100% by weight, the proportion of the first polymer being 20 to 90% by weight, and the proportion of the second polymer being 10 to 80% by weight, the proportion of the aromatic vinyl compound being 20% by weight or more by weight, the processing aid for a vinyl chloride resin composition.
[0008] <2> The composition further comprises a third polymer which is an outermost layer covering the first polymer and / or the second polymer, and the third polymer has a Tg of -40 to 60°C and is composed of 30 to 90% by weight of an alkyl acrylate and 10 to 70% by weight of another copolymerizable vinyl compound, with the whole of the third polymer being 100% by weight. <1> 2. A processing aid for a vinyl chloride resin composition according to claim 1 .
[0009] <3> The first polymer has a weight average molecular weight of 1,000,000 to 2,000,000, and is composed of 80 to 100% by weight of an alkyl methacrylate and 0 to 20% by weight of other copolymerizable vinyl compounds, with the total of the first polymer being 100% by weight. The second polymer has a weight average molecular weight of 15,000 to 150,000, and is composed of 5 to 40% by weight of a vinyl cyanide compound, 60 to 85% by weight of an aromatic vinyl compound and 0 to 20% by weight of other copolymerizable vinyl compounds, with the total of the second polymer being 100% by weight. The processing aid is composed of 40 to 80% by weight of the first polymer and 20 to 60% by weight of the second polymer, with the total of the first polymer and the second polymer being 100% by weight. <1> or <2> 2. A processing aid for a vinyl chloride resin composition according to claim 1 .
[0010] <4> The first polymer is 100% by weight of the entire first polymer, and is composed of 90 to 100% by weight of an alkyl methacrylate and 0 to 10% by weight of other copolymerizable vinyl compounds. The second polymer has a weight average molecular weight of 20,000 to 80,000. The processing aid is 100% by weight of the total of the first polymer and the second polymer, and the proportion of the first polymer is 50 to 70% by weight and the proportion of the second polymer is 30 to 50% by weight. <3> 2. A processing aid for a vinyl chloride resin composition according to claim 1 .
[0011] <5> 100 parts by weight of vinyl chloride resin, <1> ~ <4> 2. A vinyl chloride resin composition comprising 0.1 to 20 parts by weight of the processing aid according to claim 1.
[0012] <6> <5> A molded article obtained by molding the vinyl chloride resin composition described above. Effect of the Invention
[0013] According to the present invention, it is possible to provide a processing aid for a vinyl chloride resin composition which maintains good transparency and yellowness while achieving both surface properties (free from flow marks and fish eyes) and gloss of a molded article of the vinyl chloride resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims, and embodiments and examples obtained by appropriately combining the technical means disclosed in different embodiments and examples are also included in the technical scope of the present invention. In addition, all academic literature and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more and B or less."
[0015] <Processing aids> The processing aid for vinyl chloride resin compositions of the present invention (hereinafter also simply referred to as processing aid) contains at least a first polymer having a structural unit consisting of an alkyl methacrylate and a second polymer having a structural unit consisting of an aromatic vinyl compound. In this specification, the term "processing aid for vinyl chloride resin compositions" refers to an additive that can promote gelation during molding of a vinyl chloride resin composition and improve the surface properties of a molded product without substantially reducing the properties of the vinyl chloride resin.
[0016] In the processing aid, the total of the first polymer and the second polymer is 100% by weight, the proportion of the first polymer is 20 to 90% by weight, and the proportion of the second polymer is 10 to 80% by weight. Preferably, the proportion of the first polymer is 40 to 80% by weight, the proportion of the second polymer is 20 to 60% by weight, and more preferably, the proportion of the first polymer is 50 to 70% by weight, and the proportion of the second polymer is 30 to 50% by weight.
[0017] In the processing aid, the processing aid is 100% by weight, and the proportion of the aromatic vinyl compound is 20% by weight or more from the viewpoint of maintaining the advantage of raw material price and the improvement of surface properties of the molded article. From the above viewpoint, the proportion of the aromatic vinyl compound is preferably 22 to 60% by weight, more preferably 23 to 50% by weight, even more preferably 24 to 40% by weight, and particularly preferably 25 to 35% by weight. In addition, the aromatic vinyl compound in this paragraph refers to the entire aromatic vinyl compound contained in the processing aid, and in addition to the aromatic vinyl compound contained in the second polymer, when the first polymer and / or the third polymer contain an aromatic vinyl compound, it also includes the aromatic vinyl compound contained in the first polymer and / or the third polymer.
[0018] The present inventors have found that when a processing aid consisting of only one of the first polymer and the second polymer is used for a vinyl chloride resin composition, it is difficult to obtain a molded article having both good gloss and good surface properties (flow marks, fish eyes).The inventors have also found that a processing aid containing both the first polymer and the second polymer, each of which has a specific composition, ratio, and weight average molecular weight, can obtain a molded article having both good gloss and good surface properties.
[0019] In this specification, the term "flow mark" refers to a streaky or striped pattern that remains on the surface of a molded product when a part of a molten resin mass generated in a gap between rolls during molding of a vinyl chloride resin composition passes through the gap. Also, the term "fish eye" is defined as a spherical or elliptical foreign body formed by agglomeration of a processing aid that does not disperse in the vinyl chloride resin and has a maximum length L of 50 μm or more.
[0020] The processing aid preferably has a granular structure, more preferably contains the first polymer and the second polymer in one particle, and particularly preferably exists independently in one particle without being chemically bonded to each other. That is, the processing aid preferably does not have a crosslinked structure. The structure of the processing aid in the vinyl chloride resin composition is not particularly limited, and may be a granular structure or a linear structure.
[0021] When the processing aid has a granular structure, the volume average particle diameter of the processing aid is preferably 0.05 μm to 0.5 μm, more preferably 0.07 μm to 0.3 μm, and even more preferably 0.1 μm to 0.2 μm, from the viewpoints of particle stability during production and polymerization rate (productivity). The volume average particle diameter may be measured by measuring the powdered processing aid, or may be measured by measuring the processing aid in the latex as described later.
[0022] The processing aid may be composed of only the first polymer and the second polymer, but from the viewpoint of the granulation property of the processing aid, it may further contain a third polymer in addition to the first polymer and the second polymer. In that case, the third polymer becomes the outermost layer covering the first polymer and / or the second polymer. In addition, each polymer may have a single-layer structure or a multi-layer structure. In other words, the first polymer, the second polymer, and the third polymer may each have a single-layer structure or a multi-layer structure.
[0023] In the processing aid, the content of the third polymer is preferably 1 to 50 parts by weight, more preferably 5 to 30 parts by weight, and even more preferably 8 to 15 parts by weight, relative to 100 parts by weight of the total of the first polymer and the second polymer, from the viewpoint of the balance between granulation ability and cost.
[0024] <First polymer> The first polymer has a weight average molecular weight of 600,000 to 4,000,000. From the viewpoint of achieving a good balance between processability and gloss and surface properties of a molded article, the weight average molecular weight of the first polymer is preferably 700,000 to 3,500,000, more preferably 800,000 to 2,500,000, and even more preferably 1,000,000 to 2,000,000.
[0025] The first polymer is composed of 60 to 100% by weight of alkyl methacrylate and 0 to 40% by weight of other copolymerizable vinyl compounds (i.e., other vinyl compounds copolymerizable with alkyl methacrylate), based on the total weight of the first polymer being 100%. The first polymer contains alkyl methacrylate, which has high compatibility with vinyl chloride resins, and thus the processability and gloss of the molded product can be improved. From the above viewpoint, the first polymer is preferably composed of 70 to 100% by weight of alkyl methacrylate and 0 to 30% by weight of other copolymerizable vinyl compounds, more preferably 80 to 100% by weight of alkyl methacrylate and 0 to 20% by weight of other copolymerizable vinyl compounds, and even more preferably 90 to 100% by weight of alkyl methacrylate and 0 to 10% by weight of other copolymerizable vinyl compounds, based on the total weight of the first polymer being 100%.
[0026] Examples of the alkyl methacrylate include linear alkyl methacrylates having 1 to 20 carbon atoms, such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, nonyl methacrylate, decyl methacrylate, undecyl methacrylate, dodecyl methacrylate, tridecyl methacrylate, tetradecyl methacrylate, pentadecyl methacrylate, hexadecyl methacrylate, and octyl methacrylate; isopropyl methacrylate, isobutyl methacrylate, s-butyl methacrylate, t-butyl methacrylate, isopentyl methacrylate, 2-ethyl methacrylate, and the like. branched alkyl methacrylates having 3 to 20 carbon atoms, such as isohexyl methacrylate, isoondecyl methacrylate, isododecyl methacrylate, isotridecyl methacrylate, isotetradecyl methacrylate, isopentadecyl methacrylate, isohexadecyl methacrylate, isoheptadecyl methacrylate, and isooctadecyl methacrylate; and cyclic alkyl methacrylates having 3 to 20 carbon atoms, such as cyclopropyl methacrylate, cyclobutyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cyclooctyl methacrylate, and cyclodecyl methacrylate. These may be used alone or in combination of two or more.
[0027] The number of carbon atoms in the alkyl group of the alkyl methacrylate is preferably 1 to 14, more preferably 1 to 12, still more preferably 1 to 10, still more preferably 1 to 8, and particularly preferably 1 to 6. Of the above, linear alkyl methacrylates are more preferred, and methyl methacrylate and ethyl methacrylate are further preferred.
[0028] Other vinyl compounds copolymerizable with alkyl methacrylates include linear alkyl acrylates having 1 to 20 carbon atoms, such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, nonyl acrylate, decyl acrylate, undecyl acrylate, dodecyl acrylate, tridecyl acrylate, tetradecyl acrylate, pentadecyl acrylate, and hexadecyl acrylate; isopropyl acrylate, ... Acrylic acids having 3 to 20 carbon atoms, such as propyl acrylate, isobutyl acrylate, s-butyl acrylate, t-butyl acrylate, isopentyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, isononyl acrylate, isodecyl acrylate, isoundecyl acrylate, isododecyl acrylate, isotridecyl acrylate, isotetradecyl acrylate, isopentadecyl acrylate, isohexadecyl acrylate, isoheptadecyl acrylate, and isooctadecyl acrylate, Branched alkyl acrylates; cyclic alkyl acrylates having 3 to 20 carbon atoms, such as cyclopropyl acrylate, cyclobutyl acrylate, cyclopentyl acrylate, cyclohexyl acrylate, cyclooctyl acrylate, and cyclodecyl acrylate; aryl methacrylates, such as phenyl methacrylate and methylphenyl methacrylate; aralkyl methacrylates, such as benzyl methacrylate; unsaturated acid anhydrides, such as maleic anhydride, itaconic anhydride, and citraconic anhydride; unsaturated acids, such as acrylic acid and methacrylic acid; Imide compounds of α,β-unsaturated dicarboxylic acids, such as maleimide, N-methylmaleimide, N-butylmaleimide, N-(p-methylphenyl)maleimide, N-phenylmaleimide, and N-cyclohexylmaleimide; epoxy group-containing unsaturated compounds, such as glycidyl methacrylate and allyl glycidyl ether; unsaturated carboxylic acid amides, such as acrylamide and methacrylamide; amino group-containing unsaturated compounds, such as acrylamine, aminomethyl methacrylate, amino ether methacrylate, aminopropyl methacrylate, and aminostyrene;Examples of the unsaturated compounds include hydroxyl group-containing unsaturated compounds such as 3-hydroxy-1-propene, 4-hydroxy-1-butene, cis-4-hydroxy-2-butene, trans-4-hydroxy-2-butene, 3-hydroxy-2-methyl-1-propene, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, and hydroxystyrene; and oxazoline group-containing unsaturated compounds such as vinyloxazoline. These may be used alone or in combination of two or more.
[0029] The number of carbon atoms in the alkyl group of the alkyl acrylate is preferably 1 to 14, more preferably 1 to 12, still more preferably 1 to 10, still more preferably 1 to 8, and particularly preferably 1 to 6. Of the above, linear alkyl acrylates are more preferred, with ethyl acrylate, propyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate being more preferred, and butyl acrylate being particularly preferred.
[0030] <Second double combination> The second polymer has a weight average molecular weight of 10,000 to 400,000. When only the first polymer, which is a high molecular weight substance, is added to a vinyl chloride resin composition for general sheet applications, the melt viscosity becomes too high, and flow marks and fish eyes tend to worsen. However, by using the second polymer, which has a relatively low molecular weight, together with the first polymer, flow marks and fish eyes can be improved. From this viewpoint, the weight average molecular weight of the second polymer is preferably 15,000 to 150,000, more preferably 15,000 to 120,000, further preferably 15,000 to 100,000, and particularly preferably 20,000 to 80,000.
[0031] The second polymer is composed of 30 to 90% by weight of an aromatic vinyl compound and 10 to 70% by weight of other copolymerizable vinyl compounds (i.e., other vinyl compounds copolymerizable with aromatic vinyl compounds), with the entire second polymer being taken as 100% by weight. By containing an aromatic vinyl compound, the second polymer can have a lower melt viscosity and reduce flow marks and fish eyes, as compared with a processing aid containing a large amount of methyl methacrylate, for example. From the above viewpoint, it is preferable that the entire second polymer is taken as 100% by weight, and the aromatic vinyl compound is 50 to 90% by weight and the other vinyl compounds copolymerizable with aromatic vinyl compounds are 10 to 50% by weight.
[0032] Examples of aromatic vinyl compounds include styrene, α-methylstyrene, p-methylstyrene, monobromostyrene, dibromostyrene, tribromostyrene, and chlorostyrene. From the viewpoint of raw material cost, styrene is preferred. These compounds may be used alone or in combination of two or more.
[0033] Other vinyl compounds copolymerizable with aromatic vinyl compounds include the compounds exemplified in the first polymer and vinyl cyanide compounds. As vinyl cyanide compounds, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. These compounds may be used alone or in combination of two or more.
[0034] From the viewpoints of processability, transparency and yellowness of a molded product, the second polymer is preferably composed of 5 to 40% by weight of a vinyl cyanide compound, 60 to 85% by weight of an aromatic vinyl compound, and 0 to 20% by weight of other copolymerizable vinyl compounds (i.e., other vinyl compounds copolymerizable with the vinyl cyanide compound and the aromatic vinyl compound) based on the entire second polymer as 100% by weight. The proportion of the vinyl cyanide compound is more preferably 10 to 28% by weight, and even more preferably 15 to 25% by weight. The proportion of the aromatic vinyl compound is more preferably 65 to 85% by weight, and even more preferably 70 to 85% by weight.
[0035] <Third polymer> The Tg of the third polymer is preferably in the range of -40°C to 60°C, more preferably -30°C to 40°C, and even more preferably -25°C to 20°C, from the viewpoint of improving the granulation property of the processing aid. From the viewpoint of lowering the Tg of the processing aid and improving the granulation property, the third polymer is preferably composed of 30 to 90% by weight of alkyl acrylate and 10 to 70% by weight of other copolymerizable vinyl compounds (i.e., other vinyl compounds copolymerizable with alkyl acrylate), and more preferably composed of 50 to 80% by weight of alkyl acrylate and 20 to 50% by weight of other copolymerizable vinyl compounds, based on the entire third polymer being 100% by weight. As the alkyl acrylate, the compounds exemplified in the above-mentioned first polymer and second polymer can be used in the same manner. As the other vinyl compounds copolymerizable with alkyl acrylate, the compounds exemplified in the above-mentioned second polymer and aromatic vinyl compounds can be used in the same manner.
[0036] <Method of manufacturing processing aids> The processing aid can be obtained by a polymerization method using water as a medium, such as emulsion polymerization or suspension polymerization, from the viewpoints of ease of recovery, low odor of the polymer, handling properties, blocking resistance, and economic efficiency. Among these, emulsion polymerization is more preferred from the viewpoint of dispersibility in vinyl chloride resins. Furthermore, emulsion polymerization, soap-free emulsion polymerization, and drop suspension polymerization, which can obtain particle structures, are particularly preferred polymerization methods for obtaining two or more polymer structures.
[0037] According to one embodiment, first, a monomer, an emulsifier, a radical polymerization agent, etc. constituting the first polymer are added to water and polymerized to form a particulate first polymer. Next, a monomer, an emulsifier, a radical polymerization agent, a chain transfer agent, etc. constituting the second polymer are added to the system containing the particulate first polymer and polymerized further to form a second polymer. Furthermore, a monomer, an emulsifier, a radical polymerization agent, etc. constituting the third polymer are added and polymerized further to form a third polymer as the outermost layer. In this manner, the processing aid can be produced. However, the order of forming the first polymer and the second polymer is not limited to this, and the first polymer may be formed after forming the second polymer.
[0038] As the emulsifier used in the emulsion polymerization method, a conventionally known one can be used, and examples thereof include anionic emulsifiers such as fatty acid salts, alkyl sulfate ester salts, alkylbenzene sulfonate salts, alkyl phosphate ester salts, and sulfosuccinic acid diester salts; cationic emulsifiers such as alkylamine salts; and nonionic emulsifiers such as polyoxyethylene alkyl ethers and polyoxyethylene fatty acid esters. Among them, from the viewpoint of polymerization stability, anionic emulsifiers are preferred, fatty acid salts and sulfosuccinic acid diester salts are more preferred, and semi-hardened beef tallow fatty acid potassium and dioctyl sodium sulfosuccinate are even more preferred. These may be used alone or in combination of two or more. In addition, disodium salt of ethylenediaminetetraacetic acid, sodium formaldehyde sulfoxylate, ferrous sulfate, etc. may be used as a polymerization promoter, sodium sulfate, etc. may be used as a viscosity adjuster for latex, and sodium hydroxide, etc. may be used as a pH adjuster.
[0039] The weight average molecular weights of the first polymer and the second polymer can be adjusted by changing the monomer ratios contained therein, and can also be adjusted by changing the amounts of the radical polymerization agent and the chain transfer agent used as needed, the polymerization temperature, the polymerization time, etc.
[0040] Examples of radical polymerization agents that can be used in the emulsion polymerization method include organic hydroperoxides such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, paramenthane hydroperoxide, and t-butyl peroxylaurate; redox initiators that combine an oxidizing agent made of the organic hydroperoxides with a reducing agent such as sulfite, hydrogen sulfite, thiosulfate, first metal salt, and sodium formaldehyde sulfoxylate; persulfates such as potassium persulfate and ammonium persulfate; azo compounds such as azobisisobutyronitrile, dimethyl-2,2'-azobisisobutyrate, and 2-carbamoylazaisobutyronitrile; and organic peroxides such as benzoyl peroxide and lauroyl peroxide. Among these, the radical polymerization agent is preferably potassium persulfate.
[0041] The amount of the radical polymerization agent used is, for example, 0.0001 to 1.0 part by weight, preferably 0.0005 to 0.5 part by weight, and more preferably 0.001 to 0.1 part by weight, relative to 100 parts by weight of the monomer used. If the amount of the radical polymerization agent is large, the weight average molecular weight tends to decrease, and if the amount of the radical polymerization agent is small, the weight average molecular weight tends to increase.
[0042] <Chain transfer agent> It is preferable to use a chain transfer agent when emulsion-polymerizing the second polymer. Examples of the chain transfer agent include mercaptans such as octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-hexyl mercaptan, n-hexadecyl mercaptan, n-tetradecyl mercaptan, and t-tetradecyl mercaptan, tetraethyl thiuram sulfide, carbon tetrachloride, ethylene bromide, and hydrocarbon salts such as pentane phenyl ethane, terpenes, or acrolein, methacrolein, allyl alcohol, 2-ethylhexyl thioglycol, and α-methylstyrene dimer. Among them, the chain transfer agent is preferably a mercaptan, and more preferably t-dodecyl mercaptan. These chain transfer agents can be used alone or in combination of two or more.
[0043] The amount of the chain transfer agent used is usually 0 to 1 part by weight based on 100 parts by weight of the monomer component. When using a chain transfer agent, the amount of the chain transfer agent used is, for example, 0.001 to 3 parts by weight, preferably 0.01 to 1 part by weight, and more preferably 0.05 to 0.5 parts by weight, taking into account the balance between flow marks, fish eyes, and gloss.
[0044] <Polymerization time> The polymerization time can be changed depending on the monomer, emulsifier, radical polymerization agent, and chain transfer agent used as needed, and their amounts, and is, for example, 1 to 50 hours or 5 to 24 hours. The polymerization temperature can be adjusted depending on the monomer, emulsifier, radical polymerization agent, and optionally the chain transfer agent used and their amounts, and is, for example, 10°C to 90°C, and preferably 30°C to 80°C.
[0045] <Particle size> The volume average particle diameter of the processing aid in the latex is, for example, 0.100 μm or more and 0.500 μm or less. The volume average particle diameter can be calculated by a particle size analyzer (Nanotracwave, manufactured by Nikkiso Co., Ltd.).
[0046] <Processing> Next, the obtained latex containing the processing aid may be powdered, for example, by a coagulation method. When the processing aid is powdered, the latex obtained by the above-mentioned emulsion polymerization may be treated with a coagulation method such as salt coagulation or acid coagulation (contacting with a coagulant such as an inorganic salt (preferably a divalent inorganic salt, more preferably calcium chloride) or an acid), or the latex may be spray-dried to obtain a powder. After coagulation, the processing aid may be prepared by further performing heat treatment, dehydration, washing, drying steps, etc.
[0047] <Resin composition> The vinyl chloride resin composition of the present invention contains 100 parts by weight of vinyl chloride resin and 0.1 to 20 parts by weight of the processing aid. From the viewpoint of obtaining a good effect by adding the processing aid, the amount of the processing aid is preferably 0.1 parts by weight or more, and from the viewpoint of improving the dispersibility of the processing aid in the vinyl chloride resin, it is preferably 20 parts by weight or less. The amount of the processing aid is preferably 0.2 to 18 parts by weight, more preferably 0.3 to 15 parts by weight, and even more preferably 0.5 to 12 parts by weight, relative to 100 parts by weight of vinyl chloride resin.
[0048] If necessary, an impact resistance improver, a stabilizer, a lubricant, a plasticizer, a colorant, a filler, a foaming agent, etc. may be added to the vinyl chloride resin composition.
[0049] The vinyl chloride resin composition can be obtained by mixing various components and kneading them at, for example, 100 to 200° C. using a kneading machine such as a Banbury mixer, a kneader, a roll, a ribbon blender, or a Henschel mixer.
[0050] <Molded body> The molded article of the present invention is obtained by molding the vinyl chloride resin composition described above. For example, the kneaded vinyl chloride resin composition can be molded by extrusion molding, blow molding, injection molding, calendar molding, vacuum molding, inflation molding, or the like to obtain a molded article of the vinyl chloride resin composition. The molded article is, for example, a sheet having a thickness of 0.2 to 1.0 mm or a film having a thickness of 0.01 to 0.2 mm. When the vinyl chloride resin composition described above is applied to calendar molding, it is possible to suppress the occurrence of flow marks and fish eyes, and a sheet or film having excellent gloss, transparency, and yellowness can be obtained. In addition, the vinyl chloride resin composition described above can be used to manufacture molded articles of other known vinyl chloride resin compositions. For example, it can be suitably used for building materials such as wall materials, floor materials, window frames, wall materials, and corrugated sheets; interior and exterior materials for automobiles; packings, gaskets, hoses, pipes, joints, electric wires, cables, and the like. EXAMPLES
[0051] Examples of the present invention will be described below, but the present invention is not limited to these.
[0052] <Abbreviation> AN: Acrylonitrile St: styrene BA: Butyl acrylate MMA: Methyl methacrylate t-DM: t-dodecyl mercaptan
[0053] <Weight average molecular weight of first polymer or second polymer> The first polymer or the second polymer was dissolved in tetrahydrofuran (THF), and the weight average molecular weight of the soluble portion was determined by gel permeation chromatography (HLC-8220GPC, manufactured by Tosoh Corporation) using polystyrene as a standard (sample solution: 20 mg sample / 10 mL THF, measurement temperature: 25° C., detector: differential refractometer and UV detector, injection amount: 1 mL).
[0054] <Tg of the third polymer> The Tg of each monomer was calculated from the Tg of the homopolymer described in "Polymer Handbook Fourth Edition" by J. Brand, published by Wiley in 1998, and the Tg of the third polymer was calculated based on this.
[0055] <Sheet gloss> The sheet gloss of the vinyl chloride resin composition was evaluated as an index of sheet physical properties. 100 parts by weight of vinyl chloride resin (Kaneka Corporation, product name: Kanevinyl S-1008, average degree of polymerization 800) was mixed with 1 part by weight of the processing aid of each Example or Comparative Example, 6.0 parts by weight of impact resistance improver (Kaneka Corporation, product name Kaneace B-625), 1.0 part by weight of butyltin mercapto stabilizer (Nitto Kasei Co., Ltd.: TVS#1360), 0.5 parts by weight of internal lubricant (Emery OleoChemicals, product name: GH4), and 0.4 parts by weight of external lubricant (Emery OleoChemicals, product name: G70S) in a powder state. The resulting mixture was kneaded at a rotation speed of 17 rpm and 198°C for 2 minutes using an 8-inch test roll (Kansai Roll Co., Ltd., test roll) to prepare a test piece with a thickness of 0.4 mm. The reflectance of the obtained test piece at 60° light was measured at five points in the center of the test piece using a gloss meter manufactured by BYK Gardner, and the average value was calculated.
[0056] <Flow marks (sheet haze)> In order to evaluate the flow marks of the vinyl chloride resin composition as an index of surface properties, the haze value at both ends of the roll-formed sheet was measured. The haze value at both ends of the sheet is an index of the occurrence of flow marks, and the lower the haze value at both ends of the sheet, the more the occurrence of flow marks is suppressed. 100 parts by weight of vinyl chloride resin (Kaneka Corporation, product name: Kanevinyl S-1008, average polymerization degree 800) was mixed in a powder state with 1.6 parts by weight of the processing aid of each Example or Comparative Example, 6.0 parts by weight of impact resistance improver (Kaneka Corporation, product name Kaneace B-625), 1.0 part by weight of butyltin mercapto stabilizer (Nitto Kasei Co., Ltd.: TVS#1360), 0.5 parts by weight of internal lubricant (Emery OleoChemicals, product name: GH4), and 0.4 parts by weight of external lubricant (Emery OleoChemicals, product name: G70S). The resulting mixture was kneaded for 2 minutes at 207°C and 17 rpm using an 8-inch test roll (Kansai Roll Co., Ltd., test roll) to produce a test piece (sheet) with a thickness of 0.5 mm. In accordance with JIS-K7136, the haze value was measured at 18 points on both ends of the sheet using a haze meter (product name: NDH4000, manufactured by Nippon Denshoku Industries Co., Ltd.), and the average value was calculated.
[0057] <Number of fish eyes> As an index of surface properties, the number of fish eyes of the molded article of the vinyl chloride resin composition was measured. 100 parts by weight of vinyl chloride resin (Kaneka Corporation, product name: Kanevinyl S-1008, average degree of polymerization 800) was mixed in powder form with 10 parts by weight of the processing aid of each Example or Comparative Example, 50 parts by weight of plasticizer (J-Plus Corporation: DOP), 3.0 parts by weight of Ba / Zn stabilizer (ADEKA Corporation: AC-186), 0.5 parts by weight of lubricant (Sakai Chemical Industry Co., Ltd.: H-St), 0.4 parts by weight of titanium oxide (Sakai Chemical Industry Co., Ltd.: R-62N), and 0.02 parts by weight of carbon black (Tokai Carbon Co., Ltd.: Seast 3H). The resulting mixture was kneaded at 18 rpm and 170°C for 1 minute using an 8-inch test roll (Kansai Roll Co., Ltd., test roll) to prepare a test piece with a thickness of 0.4 mm. The number of fish eyes in an area of 3 cm x 3 cm of the test piece was visually counted.
[0058] <Total light transmittance> As an index of transparency, the total light transmittance of the vinyl chloride resin composition was measured. 100 parts by weight of vinyl chloride resin (Kaneka Corporation, product name: Kanevinyl S-1008, average degree of polymerization 800) was mixed with 3 parts by weight of the processing aid of each Example or Comparative Example, 1.0 part by weight of butyltin mercapto stabilizer (Nitto Kasei Co., Ltd.: TVS#1380), 0.5 parts by weight of internal lubricant (Emery OleoChemicals, product name: GH4), and 0.4 parts by weight of external lubricant (Emery OleoChemicals, product name: G70S) in a powder state. The resulting mixture was kneaded at 17 rpm and 165°C for 5 minutes using an 8-inch test roll (Kansai Roll Co., Ltd., test roll), and then pressed and molded with a press at 180°C for 15 minutes to produce a press plate with a thickness of 1.0 mm. A transparency test piece having a thickness of 5.0 mm, a length of 30 mm, and a width of 40 mm was prepared from this press plate. The total light transmittance was measured as an index of transparency at 23°C using the obtained test piece according to JIS K 7375 standard "Plastics - Determination of total light transmittance and total light reflectance".
[0059] <Yellow Index (YI)> The yellowness index (reflection YI) of the vinyl chloride resin composition was measured. 100 parts by weight of vinyl chloride resin (Kaneka Corporation, product name: Kanevinyl S-1008, average degree of polymerization 800) was mixed with 3 parts by weight of the processing aid of each Example or Comparative Example, 1.0 parts by weight of butyltin mercapto stabilizer (Nitto Kasei Co., Ltd.: TVS#1380), 0.5 parts by weight of internal lubricant (Emery OleoChemicals, product name: GH4), and 0.4 parts by weight of external lubricant (Emery OleoChemicals, product name: G70S) in a powder state. The resulting mixture was kneaded at a rotation speed of 17 rpm and 165°C for 5 minutes using an 8-inch test roll (Kansai Roll Co., Ltd., test roll), and then pressed and molded with a press at 180°C for 15 minutes to produce a press plate with a thickness of 1.0 mm. A test piece for yellowness testing, 5.0 mm thick, 30 mm long, and 40 mm wide, was prepared from this press plate. The yellowness of the obtained test piece was measured at 23°C according to JIS K 7373 standard "Plastics - Determination of yellowness and yellowing index".
[0060] <Comparison of weight average molecular weight of the first polymer> Example 1 1.2 parts (parts by weight, the same applies below) of sodium dioctyl succinate and 0.05 parts of sodium sulfate, which had been dissolved in water in advance, were placed in a reactor equipped with a stirrer, and water was further added to make the total amount of water 200 parts. After the atmosphere in the reactor was replaced with nitrogen to remove oxygen from the space and water, the contents were heated to 75°C with stirring.
[0061] 0.01 part of potassium persulfate was added thereto, and then 47.5 parts of methyl methacrylate and 2.5 parts of butyl acrylate were continuously added thereto over a period of 2 hours to carry out polymerization of a first polymer.
[0062] After the polymerization of the first polymer was completed, 0.1 parts of sodium dioctyl succinate and 0.02 parts of potassium persulfate were added, and then 2.6 parts of butyl acrylate, 28.9 parts of styrene, 8.5 parts of acrylonitrile, and 0.4 parts of t-dodecyl mercaptan were continuously added thereto over a period of 2 hours to polymerize the second polymer.
[0063] After the polymerization of the second polymer was completed, 0.1 parts of sodium dioctyl succinate and 0.02 parts of potassium persulfate were added, and then 7 parts of butyl acrylate and 3 parts of methyl methacrylate were continuously added over 30 minutes to polymerize the third polymer. After the addition was completed, 0.02 parts of potassium persulfate was added, and the contents were kept at 75°C and stirred for more than 1 hour to complete the polymerization, and then cooled to obtain a processing aid latex.
[0064] The latex of the processing aid obtained was added to 4 parts of a calcium chloride aqueous solution diluted to a concentration of 1% by weight at a temperature condition of 70°C, and coagulation was carried out. Then, heat treatment, dehydration, washing and drying were carried out to obtain a powder of the processing aid. Using the powder of the processing aid obtained, evaluation was carried out as a molded product of the above-mentioned vinyl chloride resin composition.
[0065] (Examples 2 to 3 and Comparative Example 1) Powders of processing aids of Examples 2 to 3 and Comparative Example 1 were obtained in the same manner as in Example 1, except that the weight-average molecular weight of the first polymer was changed according to the composition shown in Table 1. The obtained powders of processing aids were used to evaluate the above-mentioned molded articles of vinyl chloride resin compositions. The weight-average molecular weight of the first polymer was adjusted by changing the amount of potassium persulfate added during the production of the first polymer.
[0066] [Table 1]
[0067] From the results in Table 1, the higher the weight average molecular weight of the first polymer, the better the gloss of the sheet. Also, the lower the weight average molecular weight of the first polymer, the better the flow marks (sheet haze) of the sheet. Specifically, when Examples 1 to 3 are compared with Comparative Example 1, the use of the processing aids obtained in Examples 1 to 3 resulted in sheets with a good balance of gloss and flow marks and excellent fisheye properties while maintaining good transparency and yellowness. In particular, Example 1 resulted in a sheet with a better balance of gloss and flow marks. However, when the processing aid obtained in Comparative Example 1, in which the weight average molecular weight of the first polymer was increased beyond the range of the present invention, was used, the balance between gloss and flow marks became poor, and although the gloss was good, the flow marks deteriorated.
[0068] <Comparison of the ratio and composition of the first polymer> (Examples 4 to 7) Powders of the processing aid of Examples 4 to 7 were obtained in the same manner as in Example 1, except that the ratio and / or composition of the first polymer was changed according to the composition shown in Table 2. Using the obtained powders of the processing aid, evaluation was carried out as a molded article of the vinyl chloride resin composition described above.
[0069] [Table 2]
[0070] From the results in Table 2, the gloss improved as the weight ratio of methyl methacrylate in the first polymer was increased. Specifically, comparing Examples 1, 4, and 5, when the processing aids obtained in Examples 1 and 4 were used, a sheet was obtained that had a good balance between gloss and flow marks while maintaining good transparency and yellowness, and had excellent fisheye properties. Furthermore, the gloss improved as the ratio of the first polymer was increased. Specifically, comparing Examples 1, 6, and 7, when the processing aids obtained in Examples 1 and 6 were used, a sheet was obtained that had a good balance between gloss and flow marks while maintaining good transparency and yellowness, and had excellent fisheye properties.
[0071] <Comparison of composition and weight average molecular weight of the second polymer, and comparison with the product in Patent Document 1> (Examples 8 to 12, Comparative Examples 2 to 3) Powders of processing aids of Examples 8 to 12 were obtained in the same manner as in Example 1, except that the composition and / or weight average molecular weight of the second polymer was changed according to the composition shown in Table 3. The obtained powders of processing aids were used to evaluate the above-mentioned molded articles of the vinyl chloride resin composition. The weight average molecular weight of the second polymer was adjusted by changing the amount of t-dodecyl mercaptan added during the production of the second polymer.
[0072] Comparative Example 4 A processing aid corresponding to Patent Document 1 was prepared as follows: 0.5 parts (parts by weight, the same applies below) of sodium dioctyl succinate, 0.0008 parts of ferrous sulfate (FeSO4·7H2O), 0.0032 parts of disodium salt of ethylenediaminetetraacetic acid, and 0.06 parts of sodium formaldehyde sulfoxylate were dissolved in water in advance and placed in a reactor equipped with a stirrer, and water was further added to make the total amount of water 200 parts.
[0073] After the atmosphere in the reactor was replaced with nitrogen to remove oxygen from the space and water, the contents were heated to 60°C with stirring while continuously adding a mixture of 18 parts of methyl methacrylate, 6 parts of butyl acrylate, 43.4 parts of styrene, 12.6 parts of acrylonitrile, and 0.05 parts of t-butyl hydroperoxide over 170 minutes to carry out polymerization. At that time, 0.2 parts of sodium dodecylbenzenesulfonate were added at the 60th and 120th minutes of the continuous addition.
[0074] Further, a mixture of 14 parts of methyl methacrylate, 6 parts of butyl acrylate, and 0.05 parts of t-butyl hydroperoxide was continuously added thereto over a period of 50 minutes to carry out polymerization. After completion of the addition of the copolymerization components, the contents were kept at 60°C and stirring was continued for more than 1 hour to complete the polymerization, followed by cooling to obtain a processing aid latex.
[0075] The resulting processing aid was coagulated by adding 4 parts of calcium chloride diluted to 1% at 70°C, followed by heat treatment, dehydration, washing and drying to obtain a powder of the processing aid. The resulting processing aid was used to evaluate the above-mentioned vinyl chloride resin composition.
[0076] [Table 3]
[0077] From the results in Table 3, the flow marks improved as the weight ratio of acrylonitrile in the second polymer was reduced and the weight ratio of styrene was increased. Specifically, comparing Examples 1, 8, and 9, when the processing aids obtained in Examples 1 and 9 were used, sheets were obtained that had a good balance of gloss and flow marks while maintaining good transparency and yellowness, and had excellent fisheye properties.
[0078] Moreover, the lower the weight average molecular weight of the second polymer, the better the flow mark and fish eye properties. Specifically, comparing Examples 1, 10, and 11, when the processing aids obtained in Examples 1 and 10 were used, a sheet was obtained that had a better balance of gloss and flow marks while maintaining good transparency and yellowness, and had excellent fish eye properties. However, when the processing aids obtained in Comparative Examples 2 and 3, in which the weight average molecular weight of the second polymer was increased beyond the range of the present invention, were used, the fish eye properties were significantly deteriorated.
[0079] Furthermore, even though the proportion of styrene in the processing aid was within the range of the present invention, when the processing aid obtained in Comparative Example 4, in which the first polymer and the second polymer were outside the range of the present invention, was used, the gloss and fisheye properties were deteriorated. [Industrial Applicability]
[0080] One aspect of the present invention can be suitably used for producing a vinyl chloride resin composition and a molded article thereof that are excellent in surface property and gloss while maintaining good transparency and yellowness index.
Claims
1. A processing aid for a vinyl chloride resin composition, comprising a first polymer, a second polymer, and a third polymer which forms an outermost layer covering the first polymer and / or the second polymer, the first polymer has a weight average molecular weight of 600,000 to 4,000,000, and is composed of 60 to 100% by weight of an alkyl methacrylate and 0 to 40% by weight of another copolymerizable vinyl compound, with the first polymer as a whole being 100% by weight; the second polymer has a weight average molecular weight of 10,000 to 400,000, and is composed of 30 to 90% by weight of an aromatic vinyl-based compound and 10 to 70% by weight of another copolymerizable vinyl-based compound, with the whole of the second polymer being 100% by weight; the third polymer has a Tg of −40 to 60° C., and is composed of 30 to 90% by weight of an alkyl acrylate and 10 to 70% by weight of another copolymerizable vinyl compound, with the whole of the third polymer being 100% by weight; The processing aid has a ratio of the first polymer of 20 to 90% by weight and a ratio of the second polymer of 10 to 80% by weight, with the total of the first polymer and the second polymer being 100% by weight, The processing aid is a processing aid for vinyl chloride resin compositions, in which the proportion of the aromatic vinyl compound is 20% by weight or more based on 100% by weight of the processing aid.
2. the first polymer has a weight average molecular weight of 1,000,000 to 2,000,000, and is composed of 80 to 100% by weight of an alkyl methacrylate and 0 to 20% by weight of another copolymerizable vinyl compound, with the first polymer as the whole being 100% by weight; the second polymer has a weight average molecular weight of 15,000 to 150,000, and is composed of 5 to 40% by weight of a vinyl cyanide compound, 60 to 85% by weight of an aromatic vinyl compound, and 0 to 20% by weight of other copolymerizable vinyl compounds, with the whole of the second polymer being 100% by weight; 2. The processing aid for vinyl chloride resin compositions according to claim 1, wherein the ratio of the first polymer is 40 to 80% by weight and the ratio of the second polymer is 20 to 60% by weight, with the total of the first polymer and the second polymer being 100% by weight.
3. the first polymer is composed of 90 to 100% by weight of an alkyl methacrylate and 0 to 10% by weight of another copolymerizable vinyl compound, with the entire first polymer being 100% by weight; The second polymer has a weight average molecular weight of 20,000 to 80,000, 3. The processing aid for vinyl chloride resin compositions according to claim 2, wherein the total of the first polymer and the second polymer is 100% by weight, and the proportion of the first polymer is 50 to 70% by weight and the proportion of the second polymer is 30 to 50% by weight.
4. A vinyl chloride resin composition comprising 100 parts by weight of a vinyl chloride resin and 0.1 to 20 parts by weight of the processing aid according to any one of claims 1 to 3.
5. A molded article obtained by molding the vinyl chloride resin composition according to claim 4.
Citation Information
Patent Citations
Processing aid, vinyl, chloride-based resin composition using the same and production of molded article using the same composition
JP2001031826A
Particles for resin modification and vinyl chloride resin composition containing same
WO2016068239A1
Vinyl chloride resin composition
WO2016195013A1